Sex‐Related Changes in Tissue Doppler Imaging Parameters Among Patients With Acute Pulmonary Thromboembolism. (1st November 2013) - Jenab, Yaser; Ghaffari-Marandi, Neda; Safir, Azam; Ejmalian, Gita; Zoroufian, Arezou; Jalali, Arash; Sahebjam, Mohammad
Abstract : Objectives: There are few studies evaluating serial changes in tissue Doppler imaging parameters in acute pulmonary thromboembolism. We aimed to compare these changes in male and female patients separately. Methods: Between September 2010 and September 2011, 41 of 64 hemodynamically stable acute patients with pulmonary thromboembolism were included in the study. Twenty‐two healthy individuals served as a control group. Results: Compared to the control group, the acute pulmonary thromboembolism group had a lower tricuspid annular plane systolic excursion, basal peak systolic velocity of the tricuspid valvular annulus, right ventricular (RV) peak systolic strain, and RV peak systolic strain rate and a higher RV diameter, peak systolic pulmonary artery pressure, and RV myocardial performance index ( P < .05). Values for these parameters were not different between men and women in the patient group. In men, compared to admission, predischarge echocardiography showed significant improvement in the tricuspid annular plane systolic excursion (mean ± SD, 16.08 ± 4.33 versus 19.29 ± 3.74 mm; P = .002), basal tricuspid annular peak systolic velocity (10.11 ± 3.66 versus 11.66 ± 3.38 cm/s; P = .007), and peak systolic strain (−13.00% ± 14.99% versus −23.20% ± 10.23%; P = .001), whereas in women, predischarge and 3‐month follow‐up echoacrdiography showed marked improvement in the tricuspid annular plane systolic excursion (17.50 ± 4.88 versus 19.79 ± 5.58 mm; P = .021) and peak systolic strain (−15.70% ± 13.52% versus −21.01% ± 10.57%, respectively; P = .045). Female patients did not show improvement in these parameters during hospitalization. Conclusions: Patterns of changes in the RV function over time during a 3‐month follow‐up might differ between male and female patients with acute pulmonary thromboembolism, and the recovery process could be slower in women. Moreover, the midventricular peak systolic strain might be useful for serial evaluation of the recovery process.